The Influence of Cooperative Learning Models and Learning Motivation on the Skills of Reading Students in Elementary School 101883 Tanjung Morawa Sub-District - Utari Nur Wulandari; Khairil Ansari; Wisman Hadi (BIRCU, 2020)
This study aims to: (1) Know the differences in reading skills of students taught with the Cooperative Integrated Reading and Composition learning model compared to students taught with conventional learning models; (2) Knowing the difference in reading skills of students who have high learning motivation compared to students who have low learning motivation; (3) Knowing the interaction between learning models and learning motivation in influencing students' reading skills. The population in this study were the fifth grade students of Elementary school 101883, Tanjungmorawa District, Deliserdang Regency, amounting to 54 people. Data collection in this study was through questionnaires and students' reading skills tests. Hypothesis testing is done by using the Two Way Anova test. The results showed that: (1) The reading skills of students taught with the Cooperative Integrated Reading and Composition learning model were higher than those taught by conventional learning models (Fcount = 21.164 and sig. 0.000> 0.05); (2) Reading skills of students who have high learning motivation are higher than reading skills of students who have low learning motivation (Fcount = 6.756 and sig. 0.012> 0.05); (3) There is an interaction between learning models and learning motivation in influencing students' reading skills (Fcount = 7.054 and sig. 0.011> 0.05).